2019
DOI: 10.5109/2349296
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation on Mechanical Properties of Reinforced Additive Manufactured Component

Abstract: Fused deposition modelling (FDM) is the one among various additive manufacturing techniques which can fabricate component of multi material. However, the tensile strength of FDM component is naturally low and hence it is difficult to use for the engineering application. For enhancing the mechanical properties, this study explores a novel methodology by adding the high strength material in between matrix material as reinforcement in the additive structure. In this study, ABS and PLA based reinforced composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…linear dimension in X-Y plane, linear dimension Y-Z plane, radial dimension and circular dimension. Table (1)(2)(3)(4) shows the measured dimension in terms of average percentage error. It is observed that the dimensional accuracy of polyjet is better than the FDM components except along the Y-Z plane.…”
Section: Measurement Of Surface Roughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…linear dimension in X-Y plane, linear dimension Y-Z plane, radial dimension and circular dimension. Table (1)(2)(3)(4) shows the measured dimension in terms of average percentage error. It is observed that the dimensional accuracy of polyjet is better than the FDM components except along the Y-Z plane.…”
Section: Measurement Of Surface Roughnessmentioning
confidence: 99%
“…Many of the RP technologies have been developed over the past several decades [3]. Some of the techniques being commonly used for the prototyping are stereo-lithography apparatus (SLA), fused deposition modeling (FDM), selective laser sintering (SLS), poly-jet amongst many other processes [4]. In 1983 Charles (Chuck) has invented the first stereo-lithography (SLA) machine, patented in 1986 and commercial available in 1988, which is a form of additive manufacturing (AM) technology used for creating models, pattern making, scaled model etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that the prints in the upright direction deliver more strength and stiffness to the composites over the flat printed variants. In a novel attempt by Maurya et al, [25] PETG was used as fiber reinforcement in ABS and PLA matrices. This addition offers significant strength enhancement in ABS composites with increasing PETG fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…Maurya et al 5) investigated experimentally and computationally about an additive manufacturing component to enhance its mechanical properties, ABS is used for making biomedical prototypes using FDM techniques. Reinforcing a new component can increase the life of biomedical device and assist in better surgical performance.…”
Section: Discussionmentioning
confidence: 99%